La natura è di casa - Loredana La Fortuna (ZoneModa Journal, 2025)
Ettore Sottsass often stated that design has nothing to do with beauty, but rather with existence. One of the primary goals of design is to conceive and produce objects that are capable of addressing the natural needs of human beings. In recent years, however, design appears to have embraced a different mission, increasingly striving to establish a new relationship with nature through objects that unexpectedly blend natural and artificial elements. This shift ranges from the reissue of iconic objects in sustainable materials, to designs that incorporate plants and flowers into their structure, and even to products that appear natural but retain all the characteristics of artificial objects. Far from being mere aesthetic experiments, these objects provoke a deeper reflection on the relationships between nature and artifice, inside and outside, green ethics and aesthetics and the cultural significance that these dynamics assume.